The E3 ubiquitin ligase RNF6 facilitates the progression of cervical cancer by inhibiting the Hippo/Yap pathway - Yawen Liu; Juanjuan Zhou; Weiqi Liu; Yi Le; Lingling Zhang; Ziyu Zhang; Ling Zhou; Ling Li (Cell Division)
Abstract Purpose Cervical cancer (CC), a significant global health threat, necessitates comprehensive understanding for improved therapeutic interventions. Many research indicates that dysregulation of the Hippo-YAP1 pathway leads to uncontrolled proliferation and invasion of tumor cells, promoting the progression of various cancers. This article aims to elucidate the role of RNF6 in CC and its regulation of the Hippo-YAP1 signaling pathway. Methods The public tumor dataset analyses, immunohistochemistry, and western blotting were used to explore the expression of RNF6 in CC. Gain- and loss-of-function assays were conducted to elucidate the role of RNF6 in the proliferation and invasion of CC cells. Transcriptome sequencing was used to explore RNF6’s role in cervical cancer, with validation of its regulation of the Hippo-YAP1 pathway through western blotting and RT-qPCR. Co-transfection of YAP overexpression plasmids into RNF6-silenced CC cells were preformed to confirm YAP1’s pivotal role in RNF6-mediated CC progression. Animal experiments were preformed to further validate RNF6 interference’s inhibitory effect on CC proliferation in vivo. Results Clinical samples and bioinformatics analysis revealed high expression of RNF6 in CC, and closely associated with advanced FIGO (International Federation of Gynecology and Obstetrics) stage, larger tumor size, and poor prognosis. Cellular functional experiments demonstrate that RNF6 promotes the proliferation, invasion, and migration of CC cells, while knockdown of RNF6 yields the opposite effect. Transcriptome sequencing further reveals that RNF6 may promote CC progression through the Hippo-YAP signaling pathway. Western blotting and RT-qPCR further unveil that RNF6 enhances the upregulation of YAP1 protein levels, thereby activating downstream oncogenes CTGF and CYR61 transcription. Additionally, exogenous overexpression of YAP1 reverses the inhibitory effect of RNF6 silencing on CC proliferation and invasion. Furthermore, RNF6 interference significantly attenuates tumor growth in vivo experiments. Conclusion Our research reveals that RNF6 is highly expressed in CC, driving malignant progression by upregulating YAP1 protein expression and enhancing the transcription of downstream target genes CTGF and CYR61, offering potential therapeutic targets for CC treatment.